A Highly Sensitive Fluorimetric Method for Determination of Cinacalcet Hydrochloride in Tablets and Plasma via Derivatization with 7-Chloro-4- nitrobenzoxadiazole - A. Darwish, Ibrahim; M. AlShehri, Mona; A. Al-Gendy, Manal (Current Analytical Chemistry, 2013)
This study represents the first report on the development and validation of a highly sensitive fluorimetric method for determination of cinacalcet hydrochloride (CIN) in tablets and plasma. The method was based on nucleophilic substitution reaction of CIN with 7-chloro-4-nitrobenzoxadiazole (NBD-Cl) in an alkaline buffered medium (pH 9) to form a highly fluorescent derivative that exhibited maximum fluorescence intensity at 552 nm after excitation at 469 nm. The factors affecting the reaction were carefully optimized. The kinetics of the reaction was investigated, the stoichiometry of the reaction was determined, and the mechanism was postulated. The activation energy of the reaction was determined and found to be 38.77 KJ/mole. Under the optimum reaction conditions, a linear relationship with good correlation coefficient (r = 0.9999) was found between the fluorescence intensity and CIN concentrations in the range of 5—200 pg/mL. The limits of detection and quantitation were 2.2 and 6.6 pg/mL, respectively. The method was reproducible as the relative standard deviations of the results did not exceed 2%. The proposed method was successfully applied to the determination of CIN in its tablets with good accuracy; the label claim percentages were 102.81–103.39 ± 1.43–3.23% (RSD). The high sensitivity of the method allowed its successful application to the accurate determination of CIN in spiked human plasma without extraction procedures; the recovery was 102.93–104.07 ± 0.04–0.53% (RSD). The proposed method is valuable for routine application in quality control and clinical laboratories for determination of CIN.
Keywords: Cinacalcet